Diversity, morphology, and molecular phylogeny of Diatrypaceae from southern China - Li, Qi-Rui; Long, Si-Han; Lin, Yan; Wu, You-Peng; Wu, Qian-Zhen; Hu, Hong-Min; Shen, Xiang-Chun; Zhang, Xu; Wijayawardene, Nalin Nilusha; Kang, Ji-Chuan; Kumla, Jaturong; Kang, Ying-Qian (Frontiers in Microbiology, 2023)
During an investigation of Diatrypaceae from southern China, ten Xylariales-like taxa have been collected. Morphological and multi-gene analyses confirmed that these taxa reside in Diatrypaceae and represent eight novel taxa and two new records belonging to six genera (viz., Allocryptovalsa, Diatrype, Diatrypella, Paraeutypella, Peroneutypa and Vasilyeva gen. nov.). Vasilyeva gen. nov. was proposed to accommodate Vasilyeva cinnamomi sp. nov. Among the other collections, seven new species were introduced (viz., Diatrype camelliae-japonicae sp. nov., Diatrype rubi sp. nov., Diatrypella guiyangensis sp. nov., Diatrypella fatsiae-japonicae sp. nov., Paraeutypella subguizhouensis sp. nov., Peroneutypa hainanensis sp. nov., Peroneutypa qianensis sp. nov.), while two were reported as new records from China (Allocryptovalsa rabenhorstii and Diatrype enteroxantha). All species were provided with detailed descriptions and illuminations as well as phylogeny based on combined sequences of ITS and β-tubulin genes.